2010
DOI: 10.1080/03235400802476658
|View full text |Cite
|
Sign up to set email alerts
|

Rapid suppression of defence enzymes and compounds by sheath blight (Rhizoctonia solani) and sheath rot (Sarocladium oryzae) toxins in rice cell suspension cultures

Abstract: To understand the suppression mechanisms against disease resistance in rice, we took advantage of the fact that suspension cultured cells exhibit many of the defence responses that are characteristic of intact tissues. In this study we constitutively measured the Rhizoctonia solani and Sarocladium oryzae toxins, induced and suppressed levels of phenylalanine ammonia lyase, peroxidase, superoxide dismutase, phenols, catalase, b-1,3-glucanase and chitinase in rice suspension cultured cells. The addition of Rhizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Proteins play a larger role in plant defense against invading pathogens in both mechanisms (Meena et al 2021) [33] . The current study agreed with Kandan et al (2010) [24] , who reported that resistant rice plants had higher crude protein levels. Low disease incidence increases total phenol and soluble protein levels, and protein banding pattern is an important factor in developing resistance to the brown spot pathogen (Bisen et al 2015) [5] .…”
Section: Estimation Of Crude Proteinsupporting
confidence: 93%
“…Proteins play a larger role in plant defense against invading pathogens in both mechanisms (Meena et al 2021) [33] . The current study agreed with Kandan et al (2010) [24] , who reported that resistant rice plants had higher crude protein levels. Low disease incidence increases total phenol and soluble protein levels, and protein banding pattern is an important factor in developing resistance to the brown spot pathogen (Bisen et al 2015) [5] .…”
Section: Estimation Of Crude Proteinsupporting
confidence: 93%